Effects of supervision on tax compliance: Evidence from a field experiment in Austria - Katharina Gangl; Benno Torgler; Erich Kirchler; Eva Hofmann (Center for Research in Economics, Management and the Arts (CREMA), 2013)
The tax compliance literature has mainly focused on individual tax evasion rather than firm tax evasion. In general, there is a lack of field experiments on the topic, and measuring tax compliance is challenging. To address this shortcoming in the literature, we conduct a field experiment on firm tax compliance looking at newly founded firms. As a novelty we explore how firms react to closer supervision by the tax administration, looking at timely paying which has no measurement biases. Interestingly, we observe a crowding-out effect of supervision on timely paying of taxes. On the other hand, for those who were non-compliant, supervision reduced the tax amount that was due.
Keywords: H26; C93; K42; 330; tax compliance; tax evasion; field experiment; deterrence; tax enforcement; supervision